The Impact of Litigation Risk on Auditor Pricing Behavior: Evidence From Reverse Mergers - Abbott, Lawrence J.; Gunny, Katherine; Pollard, Troy (Contemporary Accounting Research, 2017)
Abstract We use reverse mergers to examine the impact of litigation risk on audit fees. In a reverse merger, a private company merges with a public company, and the private company's management takes over the resulting publicly traded firm. Reverse mergers create a unique test setting to provide estimates on the litigation risk premium because, while the litigation risk for formerly private firms whose equity becomes publicly traded increases, the remaining auditee‐ and auditor‐related characteristics remain virtually unchanged. We document a litigation risk premium of approximately 27 percent. Moreover, we document that equity dispersion impacts the audit fee pricing of litigation risk and this relation is dramatically magnified in the publicly traded realm. Finally, we find that institutional investors demand higher audit effort in the form of higher audit fees in both the private‐ and public‐equity settings.